Determinants of hypertension among productive age population - Hendriani, Berliana; Rasyid, Rosfita; Firdawati, Firdawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Hypertension is one of the non-communicable diseases that is a health problem. The incidence of hypertension is generally found in the elderly, but it does not rule out the possibility that the adolescent to adult population can also experience hypertension. Hypertension may be a silent killer where symptoms can vary in each individual and are almost equivalent to the symptoms of other diseases. Purpose: To determinants of hypertension among productive age population. Method: Quantitative research using a cross-sectional study approach. The population used as respondents in this study were all productive age individuals in the Parik Rantang Health Center working area. The sampling technique is systematic random sampling, while the number of samples required is 190 samples. Results: The proportion of hypertension in the productive age population in the working area of the Parit Rantang Health Center is (43.7%). The most dominant factor is salt consumption on the incidence of hypertension in the productive age population in the Parit Rantang Health Center working area in 2024. Conclusion: Many factors influence the risk of hypertension in the productive age population including age, gender and salt consumption. Therefore it is recommended to the productive age population to pay attention to salt consumption so that the incidence of hypertension can be prevented and controlled in the productive age population.